The analysis of feet construction versus BMI in 8-year-old boys - Beata Szczepanowska-Wołowiec; Paulina Sztandera (Kazimierz Wielki University, 2017)
Introduction.  The foot due to its complex structure provides three basic functions: supportive, locomotive and amortization. The human foot is an important static-dynamic part of the motor system. A properly shaped foot should be supported by three points: the first and the fifth metatarsal bone and the external part of the heel. Purpose of research. The aim of the study was to analyze the feet construction and find the relationships between the foot structure parameters and BMI among 8-year-old boys. Material and methods. The study involved 85 boys. The weight and the body height of the children were measured, body mass index was calculated, and the footprint using the was made. On the basis of the foot picture, the basic parameters for foot assessment as well as relations between these indicators and BMI were calculated. Subsequently, the Clarke angle, the hallux valgus angle and Wejsflog index were determined in manual way. Then the dependency between these parameters and BMI was investigated. Results. The number of lower foot arch or flat foot in the study group amounted to 53%, the transverse flat foot was observed among 17% of the studied boys feet and the hallux valgus angle beyond the norm occurred in 9% of the studied feet. There is a relationship between the Clark's angle, Wejsflog index, hallux valgus angle α and BMI of boys. Conclusions. Boys with a higher BMI have lower values of the Clark angle and the Wejsflog index which are the evidence of a lower longitudinal and transverse arch. Children with higher BMI have higher values of the angle of hallux valgus α